Drug-related problems in hospitalized patients with type 2 diabetes mellitus: A systematic review - Mohammad Hisyamuddin Awang Jihadi; Ana Yuda; Anila Impian Sukorini; Andi Hermansyah; Naeem Shafqat; Ching Siang Tan; Long Chiau Ming (Elsevier, 2023)
Introduction: Type 2 diabetes mellitus (T2DM) is one of the non-communicable diseases which continues to rise in prevalence and mortality rate throughout the years. Drug-related problems (DRPs) are more prevalent among T2DM patients especially those with co-morbidities. Objective: The objective of this study was to review and assess the prevalence and characteristics of DRPs among hospitalized type 2 diabetes mellitus patients. Methods: The systematic review of the literature was carried out using five online databases: PubMed, Scopus, Google Scholar, Web of Science, and Cochrane Library from the inception of the database until June 2022. Studies included in the review were published in English or Malay language. The data were extracted and assessed using the Joanna Briggs Institute (JBI) critical appraisal tools. Results: A total of 939 studies were identified with 20 studies that met inclusion criteria and were included in this systematic review. The overall prevalence of DRPs in all 20 studies ranged from 7% to 94%. The most common DRPs included drug-drug interaction (DDI), adverse drug reaction (ADR), therapeutic effectiveness problems, and inappropriate medication use. Conclusion: The most common drug classes involved were antidiabetics (metformin), antihypertensives, antiplatelets and antibiotics. The risk factors contributing to DRPs included the presence of comorbidities, the number of medications, and polypharmacy. To conclude, the rate of DRPs incidence in hospitalized T2DM patients was observed to be high. Further future studies with appropriate study designs and methods of detecting DRPs will be necessary to reduce and prevent DRPs occurrences.